Calculation of the Coupling Coefficient in Step-Index Multimode Polymer Optical Fibers Based on the Far-Field Measurements - Svetislav Savović; Svetislav Savović; Alexandar Djordjevich; Branko Drljača; Ana Simović; Rui Min (Frontiers in Physics, 2022)
Using the power flow equation (PFE), this article investigates mode coupling in step-index (SI) multimode (MM) polymer optical fiber (POF). This equation’s coupling coefficient was initially fine-tuned so that it could appropriately reconstruct previously recorded far-field (FF) power distributions. The equilibrium mode distribution (EMD) and steady-state distribution (SSD) in the SI MM POF were found to be obtained at lengths Lc = 15 m and zs = 41 m, respectively. These lengths are substantially shorter than their glass optical fiber counterparts. Such characterization of the investigated POF can be used in its employment as a part of the communication or sensory system. Namely, the POF’s bandwidth is inverse linear function of fiber length (z−1) below the coupling length Lc. However, it has a z−1/2 dependence beyond this equilibrium length. Thus, the shorter the coupling length Lc, the sooner transition to the regime of slower bandwidth decrease occurs. It is also important to be able to determine a modal distribution at a certain length of the POF employed as a part of optical fiber sensory system.